Alien Conspiracy Theory? Exploring Ethnicity and Drug Supply in Scotland. Issue 10 (2nd October 2020) - McLean, Robert; Holligan, Chris; Riaz, Nighet
ABSTRACT: Scholars have identified associations between ethnicity and crime. The extent to which such correlations generalize to other national domiciles, and the nuances of neighborhood criminality is unclear. Drawing upon 67 interviews with practitioners and (ex)offenders involved in drug supply, and supplemented by data sets, the article tests the validity of the generalisation, by exploring a) whether ethnicity is perceived as advantageous in the movement of drugs, and b) how indigenous organized criminal gangs (OCGs) address the encroachment of foreign OCGs on their turf. Findings suggest 'official' suppositions aren't wholly supported by evidence gained from street actors connected with criminogenic environments.